Gerakan Kader Posyandu Sadar Stunting di Provinsi Lampung - Riona Sanjaya; Hellen Febriyanti; Septika Yani Veronica; Hamid Mukhlis (Utan Kayu Publishing, 2021)
Stunting is one of the targets of the Sustainable Development Goals (SDGs). The target is to reduce the stunting rate to 40% by 2025. The incidence of stunting in children under five is one of the global nutritional problems, including in Indonesia. Indonesia ranks third with the highest prevalence in the Southeast Asia region. The average prevalence of stunting under five in Indonesia between 2005 – 2017 was 36.4%. Cadre is one of the supporters of success in monitoring the growth of toddlers. Strengthening cadres is also one of the interventions in efforts to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Cadres in Integrated Healthcare Center are community members who are available, able, and have the time to organize Integrated Healthcare Center activities voluntarily. The cadre's duties related to nutrition and health include collecting data on children under five, weighing and recording it on a health card (KMS), providing additional food, offering vitamin A and nutrition counseling. So that cadres need to always get education for things related to the community. The implementation of this community service activity is carried out by midwives and cadres in Integrated Healthcare Center in Lampung Province, to increase the knowledge capacity of cadres related to balanced nutrition, stunting, and the duties of cadres as part of stunting prevention efforts in Lampung Provinces. The results of this activity indicated an increase in knowledge of cadres before and after the counseling. Abstrak. Stunting merupakan salah satu target Sustainable Development Goals (SDGs). Target yang ditetapkan adalah menurunkan angka stunting hinga 40% pada tahun 2025. Kejadian stunting pada balita merupakan salah satu masalah gizi global, termasuk di Indonesia. Indonesia menduduki peringkat ke tiga dengan prevalensi tertinggi di regional Asia Tenggara. Rata – rata prevalensi balita stunting di Indonesia antara tahun 2005 – 2017 adalah 36,4%. Kader merupakan salah satu unsur pendukung keberhasilan dalam pemantauan pertumbuhan balita. Penguatan kader juga menjadi salah satu intervensi dalam upaya penurunan Angka Kematian Ibu (AKI) dan Angka Kematian Bayi (AKB). Kader posyandu merupakan anggota masyarakat yang bersedia, mampu, dan memiliki waktu untuk menyelenggarakan kegiatan posyandu secara sukarela. Tugas kader yang terkait dengan gizi dan kesehatan diantaranya melakukan pendataan balita, melakukan penimbangan berat badan dan mencatatnya dalam kartu menuju sehat (KMS), memberikan makanan tambahan, pemberian vitamin A dan penyuluhan gizi. Sehingga kader perlu untuk selalu mendapatkan edukasi untuk diteruskan ke masyarakat. Pelaksnaan kegiatan pengabdian kepada masyarakat ini dilakukan bekerjasama dengan bidan dan kader posyandu di Provinsi Lampung, guna meningkatkan kapasitas pengetahuan kader posyandu terkait gizi seimbang, stunting, dan tugas kader posyandu sebagai bagian dari upaya pencegahan stunting di Provinsi Lampung. Hasil pelaksanaan kegiatan ini menyatakan terdapat peningkatan pengetahuan kader posyandu sebelum dan setelah diberikan penyuluhan.